2011
DOI: 10.4028/www.scientific.net/amr.236-238.247
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Epoxidized Rubber Seed Oil

Abstract: The liquefaction of cellulose in the presence of phenol without or with sulfuric acid as catalyst was investigated. The liquefied products were characterized by GC/MS and FTIR. Results showed that reaction temperature and reaction time had obvious effects on liquefaction of cellulose. Sulfuric acid showed an excellent catalytic degradation. The chemical compositions of the liquefied products produced using sulfuric acid catalyst or not were almost identical, and the majority of the identified liquefied product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The results of this epoxidation reaction study showed that the C-O stretching peak intensity increased as the temperature increased, indicating an increase in the rate of the epoxidation reaction. This result corresponds to the epoxy value increasing with the temperature increasing from 40 ℃ to 65 ℃ reported by Huang et al [38]. This research suggests that at a temperature of 65 °C, the oxirane ring formation reaction is most efficient.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The results of this epoxidation reaction study showed that the C-O stretching peak intensity increased as the temperature increased, indicating an increase in the rate of the epoxidation reaction. This result corresponds to the epoxy value increasing with the temperature increasing from 40 ℃ to 65 ℃ reported by Huang et al [38]. This research suggests that at a temperature of 65 °C, the oxirane ring formation reaction is most efficient.…”
supporting
confidence: 80%
“…Nevertheless, the signal of olefinic protons decreases when increasing the reaction time from 6 h to 24 h. It is caused by dominant epoxidation in the system, initially due to more hydrogen peroxide content. The ring-opening reaction of the epoxidized oil takes place in the later period [38].…”
Section: Key Engineering Materials Vol 944mentioning
confidence: 99%
See 1 more Smart Citation